The Definitive Guide to HTML5 Video - Pfeiffer, Silvia; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
Plugins will soon be a thing of the past. The Definitive Guide to HTML5 Video is the first authoritative book on HTML5 video, the new web standard that allows browsers to support audio and video elements natively. This makes it very easy for web developers to publish audio and video, integrating both within the general presentation of web pages. For example, media elements can be styled using CSS (style sheets), integrated into SVG (scalable vector graphics), and manipulated in a Canvas. The book offers techniques for providing accessibility to media elements, enabling consistent handling of alternative representations of media resources. The Definitive Guide to HTML5 Video dives deep into the markup that is introduced for media element support in browsers. You$1 (Bll explore the default user interface offered through browsers for media elements, as well as the JavaScript API provided to control their behavior. You$1 (Bll also learn how to account for H.264 and Ogg Theora codecs.s
Keywords: Computer science; Computer Science; Computer Science, general